2020
DOI: 10.3389/fpsyt.2020.00543
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and Psychotic Disorder

Abstract: Polycystic ovary syndrome (PCOS), a disease that usually emerges during adolescence, is characterized by hormonal imbalance and ovarian dysfunction. The prevalence can vary between 5.6 to 21.3% in women and 6% in adolescent girls. This discrepancy is related to the population studied and the diagnostic criteria used. The underlying pathophysiology of PCOS is not fully understood, but it can lead to a number of co-morbidities, including hypertension, diabetes, dyslipidemia, and also, mental health disorders. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…One earlier meta-analysis reported that the prevalence of depression and anxiety were 36.6% and 41.9% among women suffering from PCOS [ 57 ]. It can be concluded that PCOS and its consequences are responsible for increased mental health problems of women suffering from this hormonal disease [ 58 , 59 ]. The PCOS cases are increasing in Bangladesh over the last decades due to the changed lifestyle and some other demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…One earlier meta-analysis reported that the prevalence of depression and anxiety were 36.6% and 41.9% among women suffering from PCOS [ 57 ]. It can be concluded that PCOS and its consequences are responsible for increased mental health problems of women suffering from this hormonal disease [ 58 , 59 ]. The PCOS cases are increasing in Bangladesh over the last decades due to the changed lifestyle and some other demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Generally, the condition usually begins during puberty but doesn't usually get diagnosed until later years when the condition has significantly progressed. 15 There are currently three sets of criteria for diagnosing PCOS stipulated by the US National Institutes of Health (NIH), the Rotterdam criteria, and the androgen excess society (AES). 10 Although they have slight differences, all criteria agree that oligo-or anovulation and hyperandrogenism should be present for diagnosis as well as the exclusion of other endocrine disorders.…”
Section: Pcos Was First Described In Modern Medicine By Stein Andmentioning
confidence: 99%
“…13 The prevalent theory behind the pathophysiology of PCOS is that ovarian dysfunction and hyperandrogenism is due to a defect in the feedback loop of the steroid-hormone gonadotropin-releasing hormone (GnRH). 15 The patients with the syndrome have an increased pulsatile GnRH secretion which causes increased LH pulse frequency, pulse amplitude and increased luteinizing hormone (LH)/follicle-stimulating hormone (FSH) ratios. 14 The increase in LH secretion stimulates the theca interna cells to produce androgens causing the increase in male steroid hormones seen in the condition.…”
Section: Pcos Was First Described In Modern Medicine By Stein Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Some comorbidities associated with schizophrenia are specific to women, for instance, Turner's syndrome [95] or polycystic ovaries [96]. Some are very much more common in women than in men, for instance, eating disorders, thyroid disease, autoimmune disorders, and fertility disorders [97][98][99][100].…”
Section: Non-psychiatric Comorbiditiesmentioning
confidence: 99%